Rasionalitas Janji Politik Aminullah Usman Terkait Raskin Dalam Pilkada - Yasmin Anatasya Ridhatul Aisy; Dr. Effendi Hasan, M.A (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
ABSTRAKPada masa kampanye Aminullah Usman tahun 2017 di Kota Banda Aceh, Pasangan Aminullah Usman dan Zainal Arifin telah membuat janji kampanye politik untuk memperoleh dukungan suara, salah satu janji tersebut adalah memberikan biaya tebus beras sejahtera yang dulu dikenal dengan raskin. Program Beras Miskin (Raskin) merupakan subsidi pangan sebagai bentuk upaya dari pemerintah untuk meningkatkan ketahanan pangan dan memberikan perlindungan keluarga miskin melalui pendistribusian beras yang diharapkan mampu menjangkau keluarga miskin. Aminullah Usman berjanji akan memberikan raskin kepada masyarakat sebesar 32ribu persasaran penerima manfaat. Namun, dalam realitanya yang terjadi hingga saat ini janji kampanye tersebut tidak konsisten dan belum direalisasikan oleh Aminullah Usman dan program raskin kini telah digantikan dengan program Bantuan Pangan Non Tunai (BPNT). Penelitian ini bertujuan untuk mengetahui rasionalitas janji politik Aminullah Usman terkait Raskin kepada penduduk Kota Banda Aceh dan untuk mengetahui pertimbangan Aminullah Usman dalam memenuhi janji politik pada masa kampanye. Adapun pendekatan penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data primer melalui wawancara langsung dengan informan, sedangkan data sekunder melalui dokumentasi/kepustakaan. Peneliti menggunakan teori kebenaran korespondensi. Hasil penelitian ini menunjukkan bahwa janji politik Aminullah Usman yang sudah dipaparkan kepada masyarakat sama sekali tidak berjalan, dimana seharusnya ketika seorang pemimpin telah mendapat kekuasaan maka dapat membuat suatu kebijakan sebagaimana yang telah di janjikan ketika ingin memperoleh bangku kekuasaan melalui penganggaran bersama DPRK Kota Banda Aceh. Namun, kenyataannya hingga saat ini program raskin tersebut digantikan oleh program BPNT sehingga menimbulkan rasa ketidakpuasan dan tuntutan di masyarakat. 1 Penulis/Mahasiswa Prodi Ilmu Politik, FISIP, USK2 Dosen Pembimbing UtamaKata Kunci : Aminullah Usman, Political Promises, Program of Rice for Poor (Raskin)The rationality of Aminullah Usman's political promises regarding Raskin in the Regional Head ElectionsABSTRACTDuring the political campaign period of Aminullah Usman at 2017, especially in the city of Banda Aceh, a partnership of Aminullah Usman and Zainal Arifin had made political campaign promises to gain societies’ vote supports, one of the promises was to give redemption cost for society prosperous rice which was formerly known as Raskin. The program of rice for poor (Raskin) is food subsidy as government’s effort to enhance food security and also provide poor family protection through rice distribution that is expected able to reach the poor family. Aminullah Usman promised that he would give the implemented program of Raskin to the society with the amount of thirty two thousand targeted beneficiaries. Nevertheless, reality that is happening up to now conveys that, these political campaign promises are not consistently realized at all by Aminullah Usman and his program of rice for poor is now changed into Non-Cost Food Assistance (BPNT). This research is aimed to investigate the rationality of Aminullah Usman political promises related to the program of rice for poor, especially for the citizens of Banda Aceh city, while it is also proposed to find out the consideration of Aminullah Usman in fulfilling his political promises which were told during the campaign. The approach used in this research is qualitative approach where the researcher tends to find the source by seeking for information to the related people at place. Data collection technique uses primary data collected through direct interview with a factual informant, while the secondary data is collected through literature review. Researcher uses the framework of authority theory by (Marx Weber) and political policy theory. This research objective indicates that Aminullah Usman political promises exposed to the society were not working at all; actually, when a leader has gotten his power, then he could create a policy as he had promised when he still wanted to take the power bench through the calculation with the District People Representative Council (DPRK) of Banda Aceh city. Nevertheless, reality so far shows that the program of rice for poor (Raskin) is now even replaced by the program of Non-Cost Food Assistance (BPNT) causing dissatisfaction and demands in the midst of societyKey Words : Aminullah Usman, Political Promises, Program of Rice for Poor (Raskin)